Engineering of a probiotic yeast for the production and secretion of medium-chain fatty acids antagonistic to an opportunistic pathogen Candida albicans - Ling, Hua; Liu, Ruirui; Sam, Qi Hui; Shen, Haosheng; Chai, Louis Yi Ann; Chang, Matthew Wook (Frontiers in Bioengineering and Biotechnology, 2023)
Candida albicans is an opportunistic pathogen, with its infection as one of the causes of morbidity or mortality. Notably, the probiotic yeast Saccharomyces cerevisiae var. boulardii has shown the potential to fight against Candida infections. In this study, we aimed to engineer a commercial boulardii strain to produce medium-chain fatty acids (MCFAs) with antagonistic effects against C. albicans. First, we identified and characterized a boulardii strain and created its auxotrophic strain Δura3. Next, we constructed and expressed a heterologous MCFA biosynthetic pathway under the control of inducible and constitutive promoters. Aside from examining MCFA production and secretion, we confirmed MCFAs’ effects on C. albicans’ anti-biofilm and anti-hyphal formation and the immune-modulatory effect of MCFA-containing supernatants on Caco-2 cells. We found that under constitutive promoters, the engineered boulardii strain constitutively produced and secreted a mixture of C6:0, C8:0, and C10:0. The secreted MCFAs then reduced biofilm and hyphal formations in C. albicans SC5314. We also confirmed that MCFAs upregulated the expression of virulence-related genes in SC5314. Furthermore, we found that the constitutively produced MCFAs in the supernatant induced the upregulation of immune response genes in Caco-2 cells co-cultured with SC5314, indicating MCFAs’ roles in immunomodulation. Overall, the engineered boulardii strain produced and secreted MCFAs, as well as demonstrated antagonistic effects against C. albicans SC5314 and immune-modulatory effects in Caco-2. To our knowledge, this represents the first study tackling the metabolic engineering of a commercial probiotic yeast strain to constitutively produce and secrete MCFAs showing anti-Candida effects. Our study forms the basis of the potential development of a live biotherapeutics probiotic yeast against Candida infections through metabolic engineering strategies.